Hormonal responses to a rugby match: A brief review - Slimani, M.; Cheour, F.; Moalla, W.; Baker, J. S. (The Journal of Sports Medicine and Physical Fitness, 2018)
INTRODUCTION: Rugby is an intermittent team sport, commonly stressing the endocrine system by physiological efforts. However, no review has synthesized the available literature on the hormonal responses to a rugby match. The purpose of this review was to examine the hormonal responses to a rugby match. Mediator and moderator variables for the rugby match-hormonal responses relationship were also discussed. EVIDENCE ACQUISITION: The systematic search was conducted using different databases and according to the Population/Intervention or Exposure/Comparison/Outcome(s) (PICO) criteria. EVIDENCE SYNTHESIS: The data obtained in the present review show that match contests were the moderator variable between rugby match-testosterone changes relationship. Particularly, official matches decreased pre-to-post testosterone levels by 43.9%, while simulated matches increased pre-to-post testosterone levels by 33.6%. There were no significant differences between official and simulated contests for the cortisol response to a rugby match which could be explained in part by the small numbers of included studies and participants (71 high-level male players). Thus, it has been shown that a rugby match provides considerable stress to the endocrine system, which lasts up 38-48 h into the recovery period. CONCLUSIONS: The hormonal assessment of rugby players is a valid tool for monitoring stress during a rugby match and provides the opportunity to identify how athletes cope with stress induced by a competition. The information also provides potential for various mental/recovery strategies that may contribute to performance enhancement.